UMP, ASSB establish strategic collaboration in academic and human development - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 19 May 2022 - Universiti Malaysia Pahang (UMP) and Alliance Steel (M) Sdn. Bhd. (ASSB) signed a memorandum of understanding (MoU) for academic and research collaboration that benefits both parties.